Spatio-temporal Evolution of Coastal Sabkhas in Arid Rapid Urban Development Area of Kuwait - Al-Hurban, Adeeba; Albanai, Jasem A (Faculty of Geography, Universitas Gadjah Mada, 2023)
Sabkha is the Arabic term meaning